Safety and Immunogenicity of a Stable, Cold-Adapted, Temperature-Sensitive/Conditional Lethal Enterovirus A71 in Monkey Study - Kaw Bing Chua; Qimei Ng; Tao Meng; Qiang Jia (Viruses, 2021)
Enterovirus A71 (EV-A71) and coxsackievirus A16 (CA16) are major etiological agents of hand foot and mouth disease (HFMD) in children, which may result in fatal neurological complications. The development of safe, cost effective vaccines against HFMD, especially for use in developing countries, is still a top public health priority. We have successfully generated a stable, cold-adapted, temperature sensitive/conditional lethal EV-A71 through adaptive culturing in Vero cells at incrementally lower cultivation temperatures. An additional 40 passages at an incubation temperature of 28 °C, and a temperature reversion study at an incubation temperature of 37 °C and 39.5 °C, reveals the virus’s phenotypic and genetic stability at the predefined culture conditions. Six unique mutations (two in noncoding regions and four in nonstructural protein-coding genes) in combination may have contributed to its stable phenotype and inability to fully revert to its original wild phenotype. The safety and immunogenicity of this stable, cold-adapted, temperature sensitive/conditional lethal EV-A71 was performed in six monkeys. None of the inoculated monkeys developed any obvious clinical illness except one which developed a transient spike of fever. No gross postmortem lesion or abnormal histological finding was noted for all monkeys at autopsy. No virus was reisolated although EV-A71 specific RNA was detected in serum samples collected on both day 4 and day 8 postinoculation. Only EV-A71 RNA and viral antigen were detected in the spleen homogenate and peripheral blood mononuclear cells, respectively, collected on day 4. The two remaining monkeys developed good humoral immune response on day 14 and day 30 post-inoculation.